Preoperative predictors of endometrial cancer at time of hysterectomy for endometrial intraepithelial neoplasia or complex atypical hyperplasia - Vetter, Monica Hagan (Am J Obstet Gynecol, 2019)
BACKGROUND: Endometrial intraepithelial neoplasia (EIN), also known as complex atypical hyperplasia (CAH), is a precancerous lesion of the endometrium associated with a 40% risk concurrent endometrial cancer at the time of hysterectomy. While a majority of endometrial cancers (EC) diagnosed at the time of hysterectomy for endometrial intraepithelial neoplasia are low-risk, low-stage, approximately 10% of patients ultimately diagnosed with EC will have high-risk disease that would warrant lymph node assessment to guide adjuvant therapy decisions. Given these risks, some physicians choose to refer patients to a gynecologic oncologist for definitive management. Currently, little data exists regarding preoperative factors that can predict the presence of concurrent endometrial cancer in patients with endometrial intraepithelial neoplasia. Identification of these factors may assist in the preoperative triaging of patients to general gynecology or gynecologic oncology. OBJECTIVE(S): 1) To determine if preoperative factors can predict the presence of concurrent endometrial cancer at time of hysterectomy in patients with endometrial intraepithelial neoplasia; 2) To describe the ability of preoperative characteristics to predict which patients may be at a higher risk of lymph node involvement requiring lymph node assessment at the time of hysterectomy. STUDY DESIGN: We conducted a retrospective cohort study of women undergoing hysterectomy for pathologically-confirmed endometrial intraepithelial neoplasia from January 2004 to December 2015. Patient demographics, imaging, pathology, and outcomes were recorded. The “Mayo criteria” were used to determine patients requiring LND. Unadjusted associations between covariates and progression to endometrial cancer were estimated through two-sample t-tests for continuous covariates and by logistic regression for categorical covariates. A multivariable model for endometrial cancer at the time of hysterectomy was developed using logistic regression with 5-fold cross-validation. RESULTS: Of the 1055 charts reviewed, 169 patients were eligible and included. Eighty-seven (51.5%) patients had a final diagnosis of endometrial intraepithelial neoplasia/other benign disease while eighty-two (48.5%) were ultimately diagnosed with endometrial cancer. No medical comorbidities were found to be strongly associated with concurrent endometrial cancer. Patients with endometrial cancer had a thicker average endometrial stripe compared to the patients with no endometrial cancer at time of hysterectomy (15.7 mm (SD = 9.5) vs 12.5 mm (SD = 6.4), p=0.01). Endometrial stripe of ≥ 2 cm was associated with 4.0 times the odds of concurrent endometrial cancer (95% CI: (1.5–10.0)), controlling for age. 87% of endometrial cancer cases were stage T1a (Nx or N0). Approximately 44% of patients diagnosed with endometrial cancer and an endometrial stripe ≥ 2 cm met the “Mayo criteria” for indicated lymphadenectomy compared to 22% of endometrial cancer patients with an endometrial stripe < 2 cm. CONCLUSIONS: Endometrial stripe thickness and age were the strongest predictors of concurrent endometrial cancer at time of hysterectomy for endometrial intraepithelial neoplasia. Referral to a gynecologic oncologist may be especially warranted in endometrial intraepithelial neoplasia patients with an endometrial stripe of ≥ 2 cm given the increased rate of concurrent cancer and potential need for lymph node assessment.